Validation of the communication skills attitude scale (CSAS) questionnaire in a cohort of Malaysian medical students / Noorhida Baharudin … [et al.] - Baharudin, Noorhida; Mohamed-Yassin, Mohamed-Syarif; Badlishah-Sham, Siti Fatimah; Mohd Yusof, Zamros Yuzadi; Ramli, Anis Safura (Universiti Teknologi MARA Cawangan Selangor, 2017)
The Communication Skills Attitude Scale (CSAS) assesses medical students’ attitudes towards learning communication skills and had been widely utilised all over the world. This questionnaire has 26 items framed within two subscales. This study aimed to examine the validity and reliability of the CSAS among medical students in Universiti Teknologi MARA (UiTM). Methods: This was a cross sectional questionnaire validation study among 171 first year medical students from UiTM. The CSAS had undergone content and face validation, followed by psychometric analysis using principal component analysis to assess construct validity. Internal consistency was evaluated using Cronbach alpha. Results: Factor analysis confirmed the original two-subscale structure of the CSAS (positive attitude scale, PAS and negative attitude scale, NAS). A total of 4 items were removed due to poor factor loading (1 item from PAS and 3 items from NAS). The final validated CSAS consisted of 22 items, 14 and 8 items for the PAS and NAS respectively. Cronbach alphas calculated were 0.862 for the PAS and 0.565 for the NAS. Conclusion: This study produced a validated and reliable CSAS to measure the attitude of UiTM medical students towards learning communication skills. Given the low internal reliability of the NAS in this study, future studies should include translating and validating the CSAS into the Malay language to improve its psychometric properties. Future studies should also include medical students from the three major ethnic groups and other medical schools in Malaysia to improve the generalisability of the CSAS.